A coalgebraic semantic framework for reasoning about UML: sequence diagrams - Sun, Meng (2008)
If, as a well-known aphorism states, modelling is for reasoning , this paper is an attempt to define and apply a formal semantics to UML sequence diagrams in order to enable rigourous reasoning about them. Actually, model transfor- mation plays a fundamental role in the process of software development, in general, and in model driven engineering in particular. Being a de facto standard in this area, UML is no exception, even if the number and diversity of diagrams expressing UML models makes it difficult to base its semantics on a single framework. This paper builds on previous attempts to base UML semantics in a coalgebraic setting and illustrates the application of the proposed framework to reason about composition and refactoring of sequence diagrams.